(3GdGOGQI HGdMhGaR (B:s (3GdJMajR hGdecGaCJ (B/s - (3GdYGfj, gjKe eMeOs ((3YeGf(B: s (3OGQ cfhR GdeYQaI(B, s, 2007)
(3jYQV gPG GdcJGH aj eMJhGg eGjdj eONd Edi GOGQI GdMhGaR , GdJMajR aj GdYed , GdMhGaR hGdecGaCJ , eUGOQ GdJMajR , YedjGJ GdJMajR , JMajR GdWdGH hCge eejRGJg , GHOGY GdTHGH GdMhGaR hGdYhGFb , ebJQMGJ dJUeje hJfajP GdJOGHjQ GdMGaRI s
(3HjHdjhZQGajG U(B. 199s
Keywords: (3GOGQI GdGYeGds; (3GOGQI GdGaQGOs; (3GOGQI YGeIs